2015
DOI: 10.4025/actasciagron.v37i2.19079
|View full text |Cite
|
Sign up to set email alerts
|

<b>Phytotoxic effects of aqueous leaf extracts of four Myrtaceae species on three weeds

Abstract: Research on allelopathic interactions can be useful in the search for phytotoxins produced by plants that may be employed as natural herbicides. The aim of this study was to assess the phytotoxic action of aqueous leaf extract of Blepharocalyx salicifolius, Myrcia multiflora, Myrcia splendens and Myrcia tomentosa on the germination and development of three weeds. The working hypothesis was that leaf extracts of Myrtaceae may negatively influence the development of weed species. Aqueous leaf extracts at 5 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
9
0
6
Order By: Relevance
“…The results show that the effect of ethyl propionate on the SOD and CAT activities of Z. matrella's growth also ranged from slightly stimulatory (≤0.5 mmol) to highly The data are the mean values (n = 3) ± standard error of the mean; different letters in the same column denote significant differences at p<0.05. inhibitory (≥1 mmol) in a similar fashion to the effects of A. philoxeroides extracts on Z. matrella (Table 3 and Table 4). In addition, ethyl propionate was found to have the strongest inhibition of root length in Z. matrella, which accords with the results of Imatomi et al [38], who found that the order of the inhibitory effect of allelopathic sensitivity (RI) of Codonopsis pilosula followed the sequence root dry weight > root volume > root length > height > seedling dry weight in treatments with high concentrations of ferulic acid (that is, ferulic acid has stronger inhibitory effects on the roots of Codonopsis pilosula than on the aboveground parts). The strongest inhibition of extracts of Solidago canadensis L. on the germination of rapeseed was also attributed to the presence of phenolic compounds in all treatments [39].…”
Section: Discussionsupporting
confidence: 82%
“…The results show that the effect of ethyl propionate on the SOD and CAT activities of Z. matrella's growth also ranged from slightly stimulatory (≤0.5 mmol) to highly The data are the mean values (n = 3) ± standard error of the mean; different letters in the same column denote significant differences at p<0.05. inhibitory (≥1 mmol) in a similar fashion to the effects of A. philoxeroides extracts on Z. matrella (Table 3 and Table 4). In addition, ethyl propionate was found to have the strongest inhibition of root length in Z. matrella, which accords with the results of Imatomi et al [38], who found that the order of the inhibitory effect of allelopathic sensitivity (RI) of Codonopsis pilosula followed the sequence root dry weight > root volume > root length > height > seedling dry weight in treatments with high concentrations of ferulic acid (that is, ferulic acid has stronger inhibitory effects on the roots of Codonopsis pilosula than on the aboveground parts). The strongest inhibition of extracts of Solidago canadensis L. on the germination of rapeseed was also attributed to the presence of phenolic compounds in all treatments [39].…”
Section: Discussionsupporting
confidence: 82%
“…This effect appears to be common in allelopathic studies, supported by the results obtained by Capobianco, Vestena, and Bitencourt (2009) and Al-Sherif, Hegazy, Gomaa, and Hassan (2013) all of which demonstrated that the allelopathic effects vary according to the exposed part of the plant. Imatomi et al (2015) suggested that this differential effect may be due to higher extract exposure of the roots, however, this does not apply in the current study as the shoots and roots were exposed to the extracts at the same intensity. In general, treatment with Brazilian cherry extracts affected the target species in some way, but the phytotoxicity of the fresh extract was greater than the infused extract.…”
Section: Resultsmentioning
confidence: 64%
“…Comparable effects on the root development of maize have also been observed for Azadirachta indica A. Juss (Rickli, Fortes, Silva, Pilatti, & Hutt, 2011) and Lupinus angustifolius L. (Gomes, Fortes, Silva, Bonamigo, & Pinto, 2013), at all concentrations tested. Imatomi et al (2015) evaluated the allelopathic potential of extracts of 15 Brazilian Myrtaceae species, all of which had phytotoxic effects on root development of the target species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tests were carried out in Petri disks on washed sand media covered with cotton on the bottom. Bioculture was dissolved with destiled water in 10 mL of solution with concentrations of 0, 5 and 10% (Imatomi et al, 2015), applied daily and observed after watering for 3 days. Data on liquid fertilizer contents and germination tests were analyzed using one way ANOVA.…”
Section: Methodsmentioning
confidence: 99%